2008
DOI: 10.1021/ja806021y
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Alkylative Construction of Quaternary Carbon Centers

Abstract: Protocols for the stereodefined formation of α,α-disubstituted enolates of pseudoephedrine amides are presented followed by the implementation of these in diastereoselective alkylation reactions. Direct alkylation of α,α-disubstituted pseudoephedrine amide substrates is demonstrated to be both efficient and diastereoselective across a range of substrates, as exemplified by alkylation of the diastereomeric pseudoephedrine α-methylbutyramides, where both substrates are found to undergo stereospecific replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 25 publications
0
59
0
Order By: Relevance
“…The resulting heterogeneous mixture was filtered through Celite, which was rinsed with diethyl ether. The organic phase was dried over Na 2 SO 4 and concentrated in vacuo to give a crude oil, which was chromatographed on silica gel (eluent: hexanes) to afford the title compound (139 mg, 86 %) as a colorless oil. The product was fully characterized by .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting heterogeneous mixture was filtered through Celite, which was rinsed with diethyl ether. The organic phase was dried over Na 2 SO 4 and concentrated in vacuo to give a crude oil, which was chromatographed on silica gel (eluent: hexanes) to afford the title compound (139 mg, 86 %) as a colorless oil. The product was fully characterized by .…”
Section: Methodsmentioning
confidence: 99%
“…[3] Herein we show that the practical substitution of silanes with Grignard reagents is possible in the presence of LiCl [4] as formulated in Equation (1). [5] The impressive effect of the lithium salt upon the substitution of a silane is highlighted below.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, pseudoephedrine-based a-branched amides selectively formed Z-and E-enolates upon deprotonation, as confirmed from the nOe spectra of the corresponding cyclic siloxane derivatives (Scheme 4). 34 The rationalization for the favored pre-transition state suggested that the solvated lithium alkoxide side chain and the base are positioned on opposite faces of the forming enolate, with the R-C-H bond suitably aligned for deprotonation ( Fig. 2).…”
Section: Formation Of Stereodefined Trisubstituted Enolates By Deprotmentioning
confidence: 99%
“…The condensing agents used for Methods B and C complement other reagents (1-ethyl-3-(3-dimethylaminopropyl) carbodiimide, diisopropylcarbodiimide) that are frequently used to acylate β-amino alcohols with acrylic acids. 14,15) All precursor anhydrides and acids were commercially available except for (S)-4-oxo-2-azetidinecarboxylic acid, which was synthesized by the procedure of Baldwin et al 16) We also aminated epoxide 3 with allylamine to give 6 in 67% yield. We view the terminal olefin as a convenient functional group to introduce electrophilic functionality onto the amine side chain toward making homologous analogs of 1a.…”
Section: Resultsmentioning
confidence: 99%